A Study on the Sustainable Building Technologies Considering to Performance of Greenhouse Gas Emission Reduction. (2015) - Park, Miyeon; Tae, Sungho; Suk, Sungjoon; Ford, George; Smith, Michael E.; Steffen, Robert
Abstract: The purpose of this study is to construct a database of sustainable building technologies considering the performance of greenhouse gas (GHG) emissions reductions. Through analysis of various sustainable green building certifications such as G-SEED, LEED, BREEAM, and CASBEE, sustainable technology factor categories associated with GHG reduction technologies were derived. Environmental performance and economic characteristics according to the considered sustainable building technology was examined and a model was generated. This model will be used to determine the best sustainable technologies which will support optimum building design to reduce national GHG emissions in Korea, enhance energy efficiency and preserve natural resources.